An assessment of the Philippine Leather Tannery Industry. - Siriban, Anna Bella D.; Doña, Edgar L.; Ong-Banzon, Victoria Hariette D.
From 50 tanneries recorded in 1918, the number of leather tanneries peaked to 152 tanneries in 1989. In 1996, the number of tanneries scaled down to 100 firms, mostly small and medium-sized. Geographically, Philippine tanneries can be found as far north as Ilocos Norte and as far south as Zamboanga del Sur. Seven Philippine provinces cater to the tannery industry, namely, Ilocos Norte, Ilocos Sur, Pangasinan, Bulacan, Metro Manila, Cebu and Zamboanga del Sur. Currently, many of these tanneries have banded together as an association through the Tanneries Association of the Philippines in order to collectively find means to consider holistically the common needs that affect them and addressthem as one unified entity. The issues and concerns are varied, complex and can not be tackled separate from its linkage with government and the agricultural industry. This paper attempts to accomplish an objective assessment of the industry's strengths and weaknesses in light of the opportunities and threats facing it with the end-in-view of creating interest on the many sectors that should involve themselves, if this industry is to be sustained.
Keywords: Leather tannery; Industry assessment